GIS and planning support system for Klang Valley Region, Malaysia - Muhamad Ludin, Ahmad Nazri; Yaakup, Ahris; Abu Bakar, Siti Zalina (2006)
Metropolisation process brings numerous benefits to the quality of urban life and environment but at the same time leads to problems such as uncontrolled development, urban sprawl, congestion and the increasing cost of public services to cater for new infrastructure. Apart from that socio-economic disparity between regions becomes more significant, compounded by increasing rate urban poverty and the risk of social exclusion. Thus, the activities of controlling and monitoring urban development are crucial. The understanding of the urban system that promotes urban growth is also imperative for the purpose of policy making, formulating development strategies as well as development plans preparation. Apparently, the dynamic nature of planning and monitoring of development such as in Klang Valley, the fastest growing region in Malaysia, necessitates a â€˜toolâ€™ for continuous monitoring, evaluation and analysis of current environment as well as assessing the capacity for future development. As such, the development of a comprehensive database and GIS-based planning application under the project named â€œApplication of Geographical Information System for Klang Valley Region (AGISwlk)â€? was initiated in 1995. The implementation of AGISwlk had been directed toward organisation of the system to facilitate immediate query and analysis, monitoring of development planning as well as spatial modelling. The project had since undergone intensive enhancement in its database structure, data quantity and quality, analysis approach and techniques as well as system customisation and integration to include the ability to provide alternatives in development scenarios. The application was further enhanced to include the development of AGISwlk web-based GIS application and establishment of the Integrated Land use Assessment (ILA) model. This paper will discuss the development, organisation and application of GIS for urban metropolitan management of Klang Valley Region, Malaysia.